Comparison of early stage electrocardiographic, echocardiographic and histopathologic results of partial pericardiectomy and thoracoscopic pericardial window techniques in an animal model - SALCI, H.; KOCATURK, M.; VOLKAN IPEK, V.; BICER, M.; YILMAZ, Z.; SAMI BAYRAM, A. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study aimed to compare early stage electrocardiographic (ECG), echocardiographic (ECHO) and histopathologic results of the pericardial surgery techniques. Partial pericardiectomy by lateral thoracotomy and thoracoscopic pericardial window techniques was performed under general anesthesia in goats (n=6), which were separated into two groups; partial pericardiectomy was performed in group I (GRI) (n=3) and thoracoscopic pericardial window was performed in group II (GRII) (n=3). ECG and ECHO examinations were performed pre- and postoperatively on days 1, 7 and 30. All experimental animals were sacrificed at the end of day 30 and macroscopic investigations were performed. Histopathological examinations were performed on the lung, visceral pleura, epicardium and myocardial tissues. ECG findings included sinus tachycardia, small complex QRS and T wave peak on day 1 in both groups., The left atrial and ventricular diameters as well as the stroke volume were lower on the 1st postoperative day in both groups. The stroke volume was lower on postoperative days 1 and 30 in GRII. The observed ejection fraction was lower in GRII and higher in GRI on postoperative day 30 compared with their baselines. Macroscopic and histopathological findings of the lung and heart tissues were more severe in GRI, but there was no meaningful variation in the epicardium or visceral pleura. There was no significant difference in the histopathological results between the groups. Although the thoracoscopic pericardial window technique seem less traumatic and better tolerated than partial pericardiectomy, our ECHO and histopathologic results indicate that both techniques can safely be performed by surgeons according to the pericardial disease indication.